Medicare Utilization and Reimbursement for Vertebroplasty and Kyphoplasty: A National Analysis From 2012–2017. Issue 24 (15th December 2020) - Lopez, Cesar D.; Boddapati, Venkat; Lombardi, Joseph M.; Cerpa, Meghan K.; Lee, Nathan J.; Mathew, Justin; Sardar, Zeeshan M.; Lenke, Lawrence G.; Lehman, Ronald A.
Abstract : Study Design: Retrospective cohort study Objective: This study seeks to identify recent trends in utilization and reimbursements of these procedures between 2012and 2017, a period which experienced a change in national guideline recommendations for these procedures. Summary of Background Data: Minimally invasive vertebral augmentation procedures, including vertebroplasty and kyphoplasty, have been typically reserved for fractures associated with refractory pain, deformity, or progressive neurological symptoms. However, controversy exists regarding the safety and effectiveness of these procedures, in particular vertebroplasty. Methods: Annual Medicare claims and payments to surgeons were aggregated at the county level to assess regional trends. Descriptive statistics and multivariate regression models were used to evaluate trends in procedure volume, utilization rates, and reimbursement rates, and to examine associations between county-specific variables and outcome variables. Results: A total of 24, 316 vertebroplasties and 138, 778 kyphoplasties were performed in the Medicare population between 2012 and 2017. Annual vertebroplasty volume fell by 48.0% from 5744 procedures in 2012 to 2987 in 2017, with a compound annual growth rate (CAGR) of −12.3%. Annual kyphoplasty volume also declined by 12.7% (CAGR −2.7%), from 24, 986 in 2012 to 21, 681 in 2017. Surgeon reimbursements for vertebral augmentation procedures increased by a weighted average of 93.7% (inflation-adjusted increase of 78.2%) between 2012 and 2017, which was primarily driven by a dramatic 113.3% (inflation-adjusted increase of 96.2%) increase in mean reimbursements for kyphoplasty procedures from an average of 895 to 1764, between 2012 and 2017, respectively. Conclusion: This large national Medicare database study found that vertebroplasty and kyphoplasty procedure volume and utilization of both procedures have declined significantly. Although average reimbursements to surgeons for vertebroplasties have significantly declined, payments for kyphoplasty procedures have risen significantly. Although vertebroplasty volume has significantly decreased, it is still being performed and being reimbursed for, in spite of its controversial role in its treatment of vertebral fractures. Level of Evidence: 3 Abstract : This study of trends in utilization and reimbursement of vertebroplasty and kyphoplasty procedures using a large national Medicare registry found that procedure volume and utilization of both procedures have declined significantly. Although average reimbursements to surgeons for vertebroplasties have significantly declined, payments for kyphoplasty procedures have risen significantly.